Pengaruh Eco-Efficiency, Carbon Emissions Disclosure, dan Profitability Terhadap Nilai Perusahaan: Studi Kasus pada Sektor Perusahaan Infrastruktur yang Terdaftar di BEI Periode 2021-2023 - Resti Kurniasari; Yuli Tri Cahyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to examine and analyze the effect of eco-efficiency, carbon emissions disclosure, and profitability on the value of the company. Hypothesis testing was conducted with a sample of 62 infrastructure companies registered with IDX-IC for the period 2021-2023. Sampling method using purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The results showed that carbon emission disclosure has an effect on the value of the company, while eco-efficiency and profitability have no effect.